Activity Test of Ethyl Acetate Fraction and N-Hexane Fraction of Tamarind Leaf Extract (Tamarindus indica L.) Against Healing Burns and Incision Wounds in Rabbits (Oryctolagus cuniculus) - Sitti Rahimah; Suwahyuni Mus; Zulkifli Zulkifli; Nurzadrina Nurzadrina; Nurhikmah Nurhikmah; Ismail Ismail; Rahmad Aksa; Nur Rahma Rumata (STIFA Makassar, 2022)
Tamarind leaf (Tamarindus indica L.) is one of the forgotten plants that has potential as a medicine for burns based on its chemical compounds such as alkaloids, flavonoids, saponins and tannins. This study aims to determine the effect of giving the ethyl acetate fraction and the n-hexane fraction of tamarind leaves on the healing of burns in rabbits (Oryctolagus cuniculus). The test was carried out using 3 rabbits for each type of treatment, namely burns and incision wounds. Each experimental animal was induced as many as 6 wounds on each back of the rabbit with the following treatments: Wound I (negative control), Wound II (bioplacenton gel), Wound III (1% n-hexane fraction), Wound IV (n-hexane fraction). 3% hexane, Wound V (1% ethyl acetate fraction) and Wound Vl (3% ethyl acetate fraction). The macroscopic observations observed included color, edema, wound diameter, scab formation and opening and epitalization. Both hexane and ethyl acetate fraction of tamarind leaf extract had activity as a burn healer at concentrations of 1% and 3%.The conclusion was that the ethyl acetate fraction of 3% tamarind leaf extract had the best activity among other treatments.